2019
DOI: 10.1109/access.2019.2920578
|View full text |Cite
|
Sign up to set email alerts
|

Physical Layer Security in Uplink NOMA Multi-Antenna Systems With Randomly Distributed Eavesdroppers

Abstract: The physical layer security of uplink non-orthogonal multiple access (NOMA) is analyzed. A stochastic geometry approach is applied to analyze the coverage probability and the effective secrecy throughput (EST) of the kth NOMA user, where a fixed or an adaptive transmission rate can be used. A protected zone around the legitimate terminals to establish an eavesdropper-exclusion area. We assume that the channel state information associated with eavesdroppers is not available at the base station. We consider that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…e security performance of the NOMA networks can be improved by invoking the protected zone and by generating noise at the BS as shown by Liu et al [7]. e physical layer security of uplink nonorthogonal multiple access is analyzed by Gerardo Gomez et al [8]. Tao et al [9] proposed a new reliable physical layer network coding and cascade-computation decoding scheme.…”
Section: Related Workmentioning
confidence: 99%
“…e security performance of the NOMA networks can be improved by invoking the protected zone and by generating noise at the BS as shown by Liu et al [7]. e physical layer security of uplink nonorthogonal multiple access is analyzed by Gerardo Gomez et al [8]. Tao et al [9] proposed a new reliable physical layer network coding and cascade-computation decoding scheme.…”
Section: Related Workmentioning
confidence: 99%
“…By introducing multi-antenna into the NOMA systems, it can achieve the advantages of multi-antenna and NOMA. Therefore, some research works have investigated the combined technology; see [34][35][36][37][38] and the references therein. Authors in [34] studied the performance of multiple-antenna NOMA and OMA, and it indicated that the performance of multiple-antenna NOMA outperforms that of multiple-antenna OMA one.…”
Section: Introductionmentioning
confidence: 99%
“…The antenna selection (AS) technology has the advantages of low cost, low complexity, high diversity gains, which can solve the computational complexity and power consumption issues caused by multiple antennas. Therefore, the combination of NOMA and AS has attracted significant attention [35][36][37][38]. In [35], the authors analyzed the secure outage performance of MISO-NOMA systems by deriving the exact analytical expressions of SOP under optimal antenna selection (OAS) and suboptimal antenna selection (SAS) schemes, and proposed an effective power allocation scheme to obtain the non-zero diversity order under the two AS schemes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, no jamming technique was utilized to improve security. The distribution of eavesdroppers was assumed to be random in [25], where the coverage probability and effective secrecy throughput (EST) of a specific user were analyzed for a fixed or an adaptive transmission rate, and only a protect zone (an eavesdropper-exclusion area) was adopted to enhance the overall EST. Different from keyless physical security in above secure UL NOMA, [26] proposed an uplink chaos NOMA transmission scheme which is based on a common key encryption to realize a secure and large-capacity uplink transmission.…”
mentioning
confidence: 99%